The Hierarchical Model of Delegated Legislation in Indonesia - Al-Fatih, Sholahuddin; Safaat, Muchamad Ali; Widiarto, Aan Eko; Al Uyun, Dhia; Nur, Muhammad (Universitas Negeri Semarang, 2023)
In a democratic rule of law like Indonesia, delegated legislation emerges as a necessity. Unfortunately, Article 8, paragraph (1) of Law Number 12 of 2011 concerning the Establishment of Laws and Regulations, in conjunction with Law Number 13 of 2022 concerning the Second Amendment to Law Number 12 of 2011, fails to articulate a clear hierarchy of delegated regulations. Employing a juridical-normative research approach encompassing statutory, historical, and conceptual dimensions, this study sheds light on the prevailing legal vacuum. The research reveals that a staggering 24,052 regulations at the level of Ministries, Agencies, and State Institutions run the risk of overlapping and becoming subject to judicial review in the Supreme Court. The definition of Delegated Legislations in Indonesia, as interpreted herein, is confined to regulations whose legal construction is executed by the executive, as long as formal legal norms continue to confer the authority of delegation in the legislative domain to implement superior regulations. This paper identifies three distinct models governing the structuring of Delegated Legislations within the hierarchy of laws and regulations in Indonesia. These models include the Hierarchical model based on the legal foundation of institution formation, the Hierarchical model based on the position of the institution, and the Hierarchical model based on the source of delegated authority in forming rules. This nuanced exploration seeks to address the complexities surrounding delegated legislation, aiming to provide clarity and coherence within the Indonesian legal framework.